2008
DOI: 10.1038/eye.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

Discrete arcs of increased fundus autofluorescence in retinal dystrophies and functional correlate on microperimetry

Abstract: Purpose To describe the occurrence of discrete arcs of increased fundus autofluorescence (FAF) associated with various retinal dystrophies and to assess their functional significance by fundus-controlled microperimetry. Methods Seven patients, three with pigmented paravenous retinochoroidal atrophy (PPRCA), one with sector retinitis pigmentosa (RP), one with typical RP, and two with macular dystrophy were assessed by retinal imaging including FAF imaging. Serial images were obtained within a review period of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
(59 reference statements)
2
31
0
Order By: Relevance
“…This is assessed by multifocal ERG [2,8,10,12] and with the visual field determined by several methods, such as kinetic perimetry [9], Humphrey static perimetry [10,13], and microperimetry [6]. The current study confirmed these results by showing that the MD of the Humphrey static perimetry correlated well with the area of and within the hyperautofluorescent ring.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is assessed by multifocal ERG [2,8,10,12] and with the visual field determined by several methods, such as kinetic perimetry [9], Humphrey static perimetry [10,13], and microperimetry [6]. The current study confirmed these results by showing that the MD of the Humphrey static perimetry correlated well with the area of and within the hyperautofluorescent ring.…”
Section: Discussionsupporting
confidence: 91%
“…That is, absent autofluorescence that represents RPE atrophy and autofluorescence that surrounds the residual area in a dot-like or patch-like pattern can be clearly detected. Additionally, an abnormal hyperautofluorescent ring in the parafoveal area has attracted much attention [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recent investigations have suggested that the hyperautofluorescent ring may be an excellent indicator of retinal dysfunction as evaluated by focal electroretinography (ERG), pattern ERG [3,8,12,13] and microperimetry [6,12].…”
Section: Introductionmentioning
confidence: 98%
“…Finally, we provide evidence that phagocytosis-mediated transfer of rod-derived toxic compounds to the retinal pigmented epithelium is required to elicit damage to that cell layer. direct toxicity to the retina (1,(26)(27)(28). Identification of the primary cause of retinal degeneration, whether it is atRAL or its condensation products, as well as determination of which cell types are initially affected comprise two particularly intriguing questions that need answers to guide the development of optimal therapeutic interventions.…”
mentioning
confidence: 99%
“…The most studied feature is a ring of increased FAF around the fovea. The hyperautofluorescent ring demarcates the preserved and damaged areas of the retina (Robson et al 2004(Robson et al , 2006Murakami et al 2008;Fleckenstein et al 2009;Lima et al 2009Lima et al , 2012. Retinal sensitivity decreases and outer retinal structures depicted on OCT become disrupted outside the ring.…”
Section: Retinitis Pigmentosamentioning
confidence: 97%